The Global Survey of the Electrical Energy Distribution System: A Review - Archana Sudhakar Talhar; Sanjay B. Bodkhe (Institute of Advanced Engineering and Science, 2019)
This paper gives a review of energy scenario in India and other countries. Today’s demand of the world is to minimize greenhouse gas emissions, during the production of electricity. Henceforth over the world, the production of electrical power is changing by introducing abundantly available renewable energy sources like sun and wind. But, because of the intermittent nature of sustainable power sources, the electrical power network faces many problems, during the transmission and distribution of electricity. For resolving these issues, Electrical Energy Storage (EES) is acknowledged as supporting technology. This paper discusses about the world electrical energy scenario with top renowned developed countries in power generation and consumption. Contribution of traditional power sources changed after the introduction of renewable energy sources like sun and wind. Worldwide Agencies are formed like International Energy Agency (IEA), The Central Intelligence Agency, (CIS) etc. The main aim of these agencies is to provide reliable, affordable and clean energy. This paper will discuss about the regulatory authority and government policies/incentives taken by different countries. At the end of this paper, author focuses on obstacles in implementation, development and benefits of renewable energy.